Efeito da pentoxifilina e do precondicionamento isquêmico na isquemia e reperfusão intestinal em ratos: estudo morfológico e biomolecular - Oliveira, Teresinha Regina Ribeiro de [UNIFESP] (2016)
Objective: To investigate histological, immunohistochemistry and molecular changes in small intestine of rats submitted to ischemia and reperfusion, handled by ischemic preconditioning and pentoxifylline. Methods: It used a sample of 30 Wistar rats EPM- 1, distributed in 5 groups, which used the superior mesenteric artery clamping to the procedures of ischemia and reperfusion. The groups were composed of 6 rats and named: Sham (laparotomy control); Ischemia and reperfusion with 0,9% saline (IRss); ischemia and reperfusion with pentoxifylline (IR_ptx); Ischemic preconditioning and ischemia and reperfusion with 0,9% salina solution (PCI_IR ss); Ischemic preconditioning and ischemia and reperfusion with pentoxifyline (PCI_IRptx). IR group ischemic time was 30 minutes and reperfusion 60 minutos. PCI time was 5 minutes ischemia and 5 minutes reperfusion to 90 minutes followed IR. The Pentoxifylline has been applied at a dose of 80 mg/kg and 0,9% saline solution (0,1 ml /dose), 5 minutes before ischemia of 30 minutes. Preconditioning groups, before the 30 minutes of ischemia, 5 minutes of ischemia and 5 minutes of reperfusion. Pulled out segments of the small intestine to a histological (staining), immunohistochemical and molecular. Were used in statistics, descriptive analysis of the data, analysis of variance (ANOVA) or Kruskall-Wallis test pos hoc ? Bonferroni. Results: Ischemic preconditioning and Pentoxifylline preserved the intestinal villus epithelial cell structure. No difference was observed between the PCI and PCI with Pentoxifylline average score. In Immunohistochemistry the caspase-3 showed more intense reaction to IR with 0,9% saline solution treatment. The Bcl-2 was positive without significant difference among averages. Molecular analysis by RT-qPCR for genes expression eNOS and iNOS was observed: the highest expression of iNOS, was significant in IRss and eNOS in PCI and Pentoxifylline treatment. Conclusions: The treatments with Pentoxifylline and PCI have been effective in preserving the small bowel cells submitted to ischemia and reperfusion. When associated strategics, there was no synergism.